The Value of Central Wave Segment in a Focal Nerve Entrapment (F-wave) Parameters of Both Median and Ulnar Nerves in Patients with Carpal Tunnel Syndrome (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study aims to assess the effect of focal median nerve injury in patients with carpal tunnel syndrome ( CTS ) on F-wave of median and ulnar nerves, determine the importance of F-wave inversion in the patients with mild CTS and find out the effect of increasing body mass index (BMI) on median nerve and its association with the severity of CTS. The study was conducted in neurophysiological unit at Merjan Medical City, in the period from September 2015 to March 2016. Including (139) patient with clinical presentation of CTS as well as positive NCS with age ranged from (20-60) years. The study also includes(139) apparently healthy person as a control group of which were matched in age, gender and BMI to patients group. F-wave of median, ulnar and median-ulnar nerve difference are highly significant (p